Prevalence and Clinical Characteristics of Metabolic Syndrome in Patients with Hypertension Attending a Primary Care Unit in Benghazi - Saleh, Adel; Adela Elamami,; Wisam Zayd, (AlQalam Journal of Medical and Applied Sciences, 2024)
Metabolic syndrome (MetS) is a cluster of cardiovascular risk factors that increase the likelihood of having cardiovascular disease and all-cause mortality. Despite the pivotal role of hypertension in MetS, statistics on the prevalence of MetS in Libyan patients with hypertension are scarce. This study aimed to ascertain the prevalence and clinical attributes of MetS in adult patients with hypertension at a primary care unit in Benghazi, Libya. A cross-sectional study, conducted from January to June 2020, and included 200 participants. Based on Modified National Cholesterol Education Program Adult Treatment Panel III guidelines, the participants were categorized into MetS and non-MetS groups. The data was collected and analyzed using SPSS Statistics software, version 27. The study population comprised 134 females and 66 males with a mean age of 51.32 ± 8.9 years. A significant proportion (73%) met the diagnostic criteria for MetS, with an average age of 52.13 ± 8.6 years, older than non-MetS patients. Females predominated in the MetS group (74.7% vs. 25.3%, p-value < 0.001), displaying a higher metabolic score than males (3.4 ± 0.9 vs. 2.8 ± 1.3, p-value = 0.003). Regarding MetS criteria, 29.5% met three, 27.5% met four, and 16% met all five criteria. MetS patients exhibited significantly higher frequencies and mean values of MetS components compared to non-MetS patients (p-value < 0.001). Notably, high waist circumference was the most prevalent criterion (84%), whereas type II diabetes mellitus had the lowest prevalence (32%). In conclusion, the study underscores the significance of early detection of MetS in patients with hypertension, ultimately contributing to more efficient healthcare delivery for this population in Libya. متلازمة الأيض هي مجموعة من عوامل الخطر القلبية الوعائية والتي تزيد من احتمالية الإصابة بأمراض القلب والأوعية الدموية ومعدل الوفيات العامة. على الرغم من الدور الحيوي لارتفاع ضغط الدم في متلازمة الأيض، إلا إن الإحصائيات حول انتشار متلازمة الأيض بين المرضى الليبيين المصابين بارتفاع ضغط الدم تعد نادرة. لذا، هدفت هذه الدراسة إلى تحديد انتشار وسمات متلازمة الأيض لدى مرضى ارتفاع ضغط الدم البالغين في وحدة للرعاية الأولية في بنغازي، ليبيا. نوع الدراسة مقطعية وتمت في الفترة من يناير إلى يونيو 2020، تضمنت 200 مشارك. باستخدام الإرشادات المعدلة لبرنامج التثقيف الوطني للكوليسترول – لوحة علاج البالغين – الجزء الثالث، تم تصنيف المشاركين إلى مجموعتين: مجموعة تعاني من متلازمة الأيض ومجموعة أخرى لا تعاني منها. تم تجميع البيانات وتحليلها باستخدام برنامج إحصائيات SPSS، الإصدار 27. تألفت عينة الدراسة من 134 فرد من الإناث و66 من الذكور بمتوسط أعمار 51.32 ± 8.9 سنة. استوفت نسبة كبيرة من المشاركين (73%) المعايير التشخيصية للمتلازمة الأيضية، بمتوسط أعمار 52.13 ± 8.6 سنة، وهو متوسط أكبر من المرضى الذين لا يعانون من متلازمة الأيض. سادت الإناث في مجموعة المرضى المصابين بمتلازمة الأيض (74.7% مقابل 25.3%، القيمة الاحتمالية أقل من 0.001)، وأيضا أظهرت الإناث درجة أيضية أعلى من الذكور (3.4 ± 0.9 مقابل 2.8 ± 1.3، القيمة الاحتمالية = 0.003). فيما يتعلق بمعايير متلازمة الأيض، فقد استوفى 29.5% ثلاثة معايير، واستوفى 27.5% أربعة معايير، فيما استوفى 16% المعايير الخمسة جميعها. كما أن المرضى المصابين بمتلازمة الأيض أظهروا تكرارات وقيمًا متوسطية أعلى وذات دلالة إحصائية لمكونات متلازمة الأيض مقارنة بالمرضى الذين لا يعانون منها (القيمة الاحتمالية أقل من 0.001). الجدير بالذكر أن قياسات محيط الخصر المرتفعة كانت المعيار الأكثر انتشارًا (84%)، في حين أن معدل انتشار مرض السكري من النوع الثاني هو الأقل .(32%) في الختام، تؤكد الدراسة على أهمية الكشف المبكر عن متلازمة الأيض في المرضى المصابين بارتفاع ضغط الدم، مما يسهم في توصيل الرعاية الصحية بكفاءة أكبر لهذه الفئة في ليبيا